2013
DOI: 10.1590/s0101-60832013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao comportamento alimentar inadequado em adolescentes escolares

Abstract: ResumoContexto: Evidências demonstram que a prevalência do comportamento alimentar inadequado (CAI) entre jovens tem aumentado nos últimos anos. Parece que a insatisfação corporal (IC), a prática excessiva de exercício físico, a composição corporal, o nível econômico (NE), além da etnia, podem ser fatores de risco para o CAI. Objetivo: Associar IC, grau de comprometimento psicológico ao exercício (GCPE), adiposidade corporal (AC), estado nutricional (EN AbstractBackground: Evidence shows that the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 24 publications
(66 reference statements)
2
24
0
11
Order By: Relevance
“…Nearly 30% of the adolescent girls in the current study were overweight or obese, which can be considered a public health problem according to some authors 8 . The study also showed higher frequency of risk behaviors for eating disorders among adolescent girls with overweight/obesity, corroborating other studies 8,26 . The girls with excess body fat thus appear to adopt food restriction, self-induced vomiting, and purging with the aim of losing weight and fitting into socially established aesthetic norms 10,12 .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Nearly 30% of the adolescent girls in the current study were overweight or obese, which can be considered a public health problem according to some authors 8 . The study also showed higher frequency of risk behaviors for eating disorders among adolescent girls with overweight/obesity, corroborating other studies 8,26 . The girls with excess body fat thus appear to adopt food restriction, self-induced vomiting, and purging with the aim of losing weight and fitting into socially established aesthetic norms 10,12 .…”
Section: Resultssupporting
confidence: 90%
“…Likewise, the current study pointed to a statistically significant relationship between body dissatisfaction and risk behaviors for eating disorders. Thus, preoccupation with weight and physical appearance appears to leave adolescent girls more prone to the adoption of food restriction and purging behaviors such as self-induced vomiting and the use of laxatives/diuretics, as demonstrated in other studies 1,5,8,20,26 .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The increase in lean mass that occurs during adolescence in males may be considered a protective factor against the development of feelings and thoughts of dislike against one's own body 7,29 . Nevertheless, some authors emphasize that the ideal body may vary according to culture 15,23,[30][31][32] . So it is possible that in some cultures, a gain in muscle mass is not good for the body image of male adolescents.…”
Section: Discussionmentioning
confidence: 99%